RELATIONSHIP BETWEEN LAW AND SOCIAL : A SOCIOLOGICAL PERSPECTIVE OF LAW - Irham Risky Aslamsyah (Academic Solution Publisher, 2024)
To achieve order and legal certainty in society, law enforcement needs to be carried out. This law enforcement is carried out, among others, by regulating the duties, functions, and authorities of institutions tasked with enforcing the law according to the authority of each institution, to achieve the creation of order and legal certainty, a good cooperation system is needed between law enforcement institutions. According to Satjipto Raharjo (Prof. Tjip), law enforcement in Indonesia is filled with complexity. One manifestation of this complexity can be stated as “law enforcement being pushed into the slow lane”. Prof. Tjip said that basically the technology of modern law uses the method of “generalization” which always has the determination to be neutral, objective, and “indiscriminate” in dealing with legal problems in society. However, in everyday reality, this method must face the “doctrine of who”, which always questions “who is the person”. As a result of this doctrine, the principle of indiscriminateness changes to the principle of “discrimination”, and it is not impossible that the legal process is also pushed into the slow lane. This research is normative legal research that uses data collection techniques, literature studies guided by primary, secondary and tertiary legal materials and then analyzed. To see how law enforcement in Indonesia is seen from a legal sociology perspective. Keywords: law enforcement, legal certainty, sociology of law